Prevalence of electrocardiographic abnormalities in young, elite Japanese athletes - Omiya, K.; Suzuki, T.; Suzuki, N.; Mitarai, T.; Takai, M.; Nakano, E.; Matsuda, H.; Musha, H. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The question as to whether or not electrocardiogram (ECG) evaluations should be performed in all athletes is still controversial. So, in this study, the prevalence of electrocardiographic abnormalities was evaluated in young, elite Japanese athletes.